2006
DOI: 10.1111/j.1467-6486.2006.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferring Organizational Learning Systems to Japanese Subsidiaries in China*

Abstract: Qualitative interviews and observations were conducted to study the cross-border transfer of organizational learning systems to the subsidiaries of five Japanese manufacturing companies operating in South China. This paper develops a holistic model of the overall process, by integrating knowledge-oriented, routine-oriented, and social/contextual perspectives, each of which plays a necessary role in explaining essential aspects. One feature of the transfer of organizational learning systems entailed arranging l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 107 publications
(156 reference statements)
0
108
0
9
Order By: Relevance
“…Brown and Duguid (2001) acknowledge that a firm's knowledge base partially draws on broader institutional structures, but exactly how these institutional structures affect situated learning and knowledge processes, and how they interact with formal organizational structures (Nicolini, Mengis and Swan, forthcoming;Roberts, 2006), has received little attention. Exceptions aside (e.g., Gherardi and Perrotta, 2011;Hong et al, 2006), the influence of broader institutional effects on situated learning still seems largely unrecognized and underplayed. As a result, we have little understanding of how social learning takes place in situ, such as how the epistemic boundaries between different communities are conditioned by wider formal structures, and the implications of this for situated learning processes.…”
Section: Situated Learning: Bringing Context Back Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown and Duguid (2001) acknowledge that a firm's knowledge base partially draws on broader institutional structures, but exactly how these institutional structures affect situated learning and knowledge processes, and how they interact with formal organizational structures (Nicolini, Mengis and Swan, forthcoming;Roberts, 2006), has received little attention. Exceptions aside (e.g., Gherardi and Perrotta, 2011;Hong et al, 2006), the influence of broader institutional effects on situated learning still seems largely unrecognized and underplayed. As a result, we have little understanding of how social learning takes place in situ, such as how the epistemic boundaries between different communities are conditioned by wider formal structures, and the implications of this for situated learning processes.…”
Section: Situated Learning: Bringing Context Back Inmentioning
confidence: 99%
“…Practice-based studies increasingly recognize that learning may be conditioned by both organizational and institutional structures (Brown and Duguid, 2001;Gherardi and Perrotta, 2011;Hong et al, 2006;Thompson, 2005). Nonetheless, the interplay between these structures has neither been systematically theorized nor empirically explored.…”
Section: Contextualizing Situated Learning In Mnes: An Explorative Frmentioning
confidence: 99%
“…Such socialization aids in orienting actors' behaviour towards collective learning (Hong et al, 2006). German Chem's emphasis on expatriate management is evident in the number of HQ personnel assigned to various subsidiaries.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, Japanese manufacturers operating in global markets have faced increasing pressures to internationalise their manufacturing. Many companies transfer the kaizen philosophy, methods and tools to their overseas subsidiaries (Abo, 1994;Aoki, 2008;Kumon & Abo, 2004), for example to North American countries (Abo, 1994;Kenney & Florida, 1993), the UK (Cole, 1979;Oliver & Wilkinson, 1992), Europe (Kumon & Abo, 2004) and China (Aoki, 2008;Hong, Easterby-Smith, & Snell, 2006;Taylor, 2001). Recent, research has shown that Japanese companies are facing problems transferring kaizen internationally due to the difficulties with adjusting to different environments .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hong et al (2006), Taylor (1999), and Aoki (2008) examined the transferability of Japanese practices to China. Saka (2004) and Oliver and Wilkinson (1992) examined the diffusion of Japanese operations, including kaizen, to the UK while Kenney and Florida (1993) looked at the transfer to the US.…”
Section: Introductionmentioning
confidence: 99%